1997
DOI: 10.1063/1.366505
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surface properties on the dielectric breakdown for polycrystalline and multilayered BaTiO3 thin films

Abstract: The dielectric reliability for polycrystalline and multilayered BaTiO 3 thin films has been evaluated using time-zero and time-dependent dielectric breakdown techniques. The histogram of dielectric breakdown for multilayered BaTiO 3 thin films showed a typical Weibull distribution in contrast to a random distribution when compared with polycrystalline BaTiO 3 thin films. The measurement resulted in that the 400 nm-thick multilayered BaTiO 3 thin film sustained about 10 5 hour-long operation at 1 MV/cm, showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…13,26,32,33 The Poole-Frenkel current is given as: The Poole-Frenkel mechanism is dominant when the leakage current is governed by a large number of charged traps in the bulk.…”
Section: (2) Effect Of Non-uniform Dielectric Layer Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…13,26,32,33 The Poole-Frenkel current is given as: The Poole-Frenkel mechanism is dominant when the leakage current is governed by a large number of charged traps in the bulk.…”
Section: (2) Effect Of Non-uniform Dielectric Layer Thicknessmentioning
confidence: 99%
“…The presence of rough interfaces and electrode discontinuities has been found to be detrimental to the miniaturization of such devices in many ways. [12][13][14][15][16] The interface roughness has also been found to influence the conductivity of metallic and semiconducting films. Previous works have revealed roughness at metal-insulator interface as sites of electric field enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Local field enhancements arising from electrode discontinuities and rough interfaces lead to a lower dielectric breakdown strength, a higher steady-state leakage current, and limited performance in terms of operating voltage, yield, and capacitance levels for specific geometries. [10][11][12][13] Prior studies by Gaillard et al and Lopes et al demonstrated the dependence of leakage current on the metal-insulator interface morphology due to local electric field enhancements around roughness. 7,14 In the past, some of these observations have been quantified by calculating the electric field distribution in the presence of electrode defects such as porosities and roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Microstructural defects such as rough interfaces and electrode discontinuities have been found to affect the device properties adversely . Local field enhancements arising from electrode discontinuities and rough interfaces lead to a lower dielectric breakdown strength, a higher steady‐state leakage current, and limited performance in terms of operating voltage, yield, and capacitance levels for specific geometries . Prior studies by Gaillard et al .…”
Section: Introductionmentioning
confidence: 99%
“…For example, random rough surfaces have been shown to influence drastically the image potential of a charge situated in the vicinity of the interface plane between vacuum and a dielectric [3], as well as inversion layers at semiconductor/oxide interfaces, because roughness induces a shift of the electronic levels [4]. Also surface/interface roughness has been shown to influence strongly the electrical conductivity of semiconducting and metallic thin film [5], as well as the electric field breakdown mechanism at a metal/insulator interface [6].…”
Section: Introductionmentioning
confidence: 99%